LANGUAGE ACQUISITION PROCESS OF A FOUR-YEAR CHILD - Cloudya Sihombing; Alemina Br. Perangin-angin (Sean Institute, 2023)
The research aimed to examine the first language acquisition of a four-year-old child from a phonological, morphological, and semantic perspective. This study used descriptive qualitative research, and the subject and object were taken from a 4-year-old child. Indeed Sheza Kanaya was the subject chosen by the researchers, and they collected the data by observing her and recording her. The analysis led the researchers to the conclusion that Sheza had appropriate communication skills. For a child to develop language, parents play a crucial role. To understand their child's language development, parents should establish interactions with their kids. In addition, the researchers advise parents to teach their kids the proper pronunciation.